العلاقة بين الفساد والاقتصاد الموازي في الجزائر دراسة قياسية تحليلية للفترة (2003-2016) - حـــــــــــــــاقة, حنـــــــــــان; حروش, رفيقة; لبزة, هشام (جامعة الوادي - University of Eloued, 2020)
يعاني الاقتصاد الجزائري منذ فترة طويلة من اختلالات كثيرة حدّت من نموه وتنوعه، ولعلّ أبرز هذه الاختلالات هو ظهور الاقتصاد الموازي وتناميه بطريقة سريعة وملفتة للانتباه، وتعود أسباب ذلك إلى انتشار الفساد بكل أنواعه وفي كل مجالاته، حيث أصبحت العلاقة وطيدة وأكيدة بين الاقتصاد الموازي والفساد في الجزائر. هدفت هذه الدراسة إلى اكتشاف العلاقة بين الفساد والاقتصاد الموازي من خلال تحليل الظاهرتين من حيث الأسباب والآثار والمؤشرات، وقياس درجة الارتباط بينهما. وتوصلت الدراسة إلى أنّ: - هناك أثر إيجابي للنشاطات غير المشروعة في الاقتصاد الموازي على الفساد؛ - هناك أثر سلبي للنشاطات المشروعة في الاقتصاد الموازي على الفساد؛ - هناك علاقة طردية موجبة بين الفساد والاقتصاد الموازي The Algerian economy suffers from long time of many imbalances reduced its growth and diversity, perhaps the most notable of these disorders is the emergence of the informal economy and growing fast and remarkable, this is due to the spread of corruption in all its forms and in all its fields, where the relationship between the parallel economy and corruption in Algeria has become steadfast. The aim of this study is to explore the relationship between shadow economy and corruption through the analysis of phenomena in terms of causes and effects and indicators, and measuring the degree of association between them. The results of the study found that: -there is a positive impact of illicit activities in the parallel economy on corruption; -there is a negative impact of legitimate activities in the parallel economy on corruption; -there is a positive correlation between corruption and the shadow economy
The relationship between corruption and the parallel economy in Algeria Analytical Standard Study in the Period (2003-2016)
مقال بمجلة الدراسات المالية والمحاسبية . مج 11 ع01. ديسمبر 2020 . جامعة الوادي
Keywords: الاقتصاد الموازي، النشاطات المشروعة، النشاطات غير المشروعة، الفساد، الاقتصاد الرسمي، نموذج الانحدار الخطي البسيط; informal economy, legitimate activities, illegal activities, corruption, the formal economy, Simple Linear Regression Model